Quantitative micro-porosity characterization using synchrotron micro-CT and xenon K-edge subtraction in sandstones, carbonates, shales and coal - Mayo, S.; Josh, M.; Nesterets, Y.; Esteban, L.; Pervukhina, Marina; Clennell, M.; Maksimenko, A.; Hall, C. (Elsevier Ltd, 2015)
Understanding porosity in rock specimens on a range of length scales is critical for assessment of geophysical properties relevant to petroleum and geothermal resources. Modern micro-CT techniques can show detail down to around a micron scale but cannot unambiguously detect porosity below the resolution limit. Here we describe the use of synchrotron K-edge subtraction using a xenon gas contrast agent to probe porosity on the micron scale in a range of rock types. Xenon, which has also been used in larger-scale studies, is an attractive contrast agent for investigating very small-scale porosity in non-sorbing specimens, and gas uptake in sorbing specimens. The K-edge subtraction method enables accurate separation of the rock and xenon signal so that xenon penetration and hence porosity can be quantitatively determined even where the individual pores themselves cannot be directly resolved.